CBT Supervision through the Eyes of Supervisors: “It’s not quite what You Think” - Juozulynas, Linas; Grigutytė, Neringa (Psichologija, 2025)
Psychotherapeutic supervision, understood as the assistance of one specialist to another in explaining the difficulties arising in professional work, is associated with professional experience and mastery, and the ways of its ‘performance’ depend not only on the supervisor, but also on the psychotherapeutic paradigm. In scientific research on the effectiveness of psychotherapeutic supervision, supervision in the field of Cognitive Behavioral Therapy, although scarcely studied, was often associated with a formal teacher-student relationship, and undeservedly little attention was paid to the experiences of supervisors. The aim of this article is to broaden the field of view by revealing the experience of Cognitive Behavioral Therapy supervision from the perspective of supervising Cognitive Behavioral Therapy psychotherapists (supervisors) in Lithuania. A qualitative study was conducted with 6 supervisors using the methods of semi-structured interviews and thematic analysis. The article reviews the research results, presenting them through three themes of the experience of Cognitive Behavioral Therapy supervision that emerged during the research: a) Supervision as knowledge sharing (methods, techniques used and how it is communicated); b) Supervision as being in a relationship; c) Supervision as experiences (personal and professional) outside the supervision session. The article provides insights based on the research conducted, which may be valuable for those preparing or reviewing supervisor training programs, and also for the psychotherapeutic supervision participants themselves (supervisors and supervisees), as well as for researchers studying psychotherapeutic supervision when choosing possible further directions of scientific research.